2021
DOI: 10.3390/ph14101005
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapies with PRRT

Abstract: Peptide receptor radionuclide therapy (PRRT) is a successful targeted radionuclide therapy in neuroendocrine tumors (NETs). However, complete responses remain elusive. Combined treatments anticipate synergistic effects and thus better responses by combining ionizing radiation with other anti-tumor treatments. Furthermore, multimodal therapies often have a balanced toxicity profile. To date, few studies have evaluated the effect of combination therapies with PRRT, some of them phase I/II trials. This review wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 79 publications
0
8
0
1
Order By: Relevance
“…Therefore, many approaches are being explored to improve therapeutic effects of PRRT, such as combination therapies, PRRT with αradionuclides, and PRRT with antagonists. [230,231]…”
Section: Prrt In Pnetsmentioning
confidence: 99%
“…Therefore, many approaches are being explored to improve therapeutic effects of PRRT, such as combination therapies, PRRT with αradionuclides, and PRRT with antagonists. [230,231]…”
Section: Prrt In Pnetsmentioning
confidence: 99%
“…With increasing efforts to increase the proportion of patients who respond to PRRT with the use of radio-sensitizers or agents to increase somatostatin receptor expression, this issue is of even greater importance. Several studies have suggested the synergistic anti-tumor effect of combining PRRT [ 376 , 377 ] with other treatments. SSAs [ 220 ], everolimus [ 378 ] and chemotherapy with capecitabine and temozolomide, can function as radio-sensitizer [ 379 ] with PRRT.…”
Section: Controversies and Uncertainties Of Predicting Therapeutic Re...mentioning
confidence: 99%
“…This can facilitate treatments adapted according to the size and distribution of metastatic deposits identified on imaging. However, this is not currently recommended; prospective, randomized studies are needed to confirm improvements in progression-free survival using combination radionuclide therapy before this is clinically implemented [129]. This also needs to be weighed against potential nephrotoxic consequences, which have been shown to be significantly more common both transiently and persistently in patients treated with 90 Y and combination 90 Y + 177 Lu compared with 177 Lu alone in a study of 807 patients [130].…”
Section: Future Directions For Prrtmentioning
confidence: 99%